Hydrodeoxygenation of karanja oil over supported nickel catalysts: influence of support and nickel loading. Issue 9 (15th December 2015) - Yenumala, Sudhakara Reddy; Maity, Sunil K.; Shee, Debaprasad
Abstract : Conversion of oxygenates increased in the order 25NiSi < 25NiAl ≤ 25NiZSM. The HDO route was dominant over (≥20 wt%) Ni/γ-Al2 O3 . The optimal conditions for the HDO route were 653 K and 25NiAl at 35 bar H2 . The properties of green diesel were comparable with light diesel oil. Abstract : Production of hydrocarbon transportation fuels from triglycerides is extremely important to reduce dependency on limited fossil fuels. The present article provides a systematic examination of hydrodeoxygenation (HDO) of karanja oil (KO) in a semi-batch reactor over supported (γ-Al2 O3, SiO2, and HZSM-5) nickel catalysts. The catalysts were associated with both dispersed and bulk nickel/nickel oxide depending on the extent of nickel loading and nature of the support. Virgin KO is composed of 76 wt% C18 fatty acids with 15 wt% oxygen. HDO of KO resulted in a wide range of alkanes (C10 –C22 ) with n -heptadecane being the major one. Transformation of KO into alkanes proceeds through three distinct routes: HDO, catalytic cracking, thermal cracking, or their combination. Highly acidic catalysts (HZSM-5 and Ni/HZSM-5) promote catalytic cracking leading to formation of a large amount of lighter alkanes. The cracking reaction becomes significant over the γ-Al2 O3 supported nickel catalyst with ≤15 wt% nickel loading at elevated temperatures. A strong metal–support interaction favored the HDO pathway over the γ-Al2 O3 supported nickel catalyst with ≥20 wt% nickel loading. About 80 wt% of KO was converted to the liquid product with physicochemical properties comparable with light diesel oil.